Shear thickening fluid as well as preparation method and application thereof

By using a combination of specific dispersion media and nanoparticles, high-performance shear thickening fluid is prepared, which solves the shortcomings of domestic shear thickening fluids in terms of dispersion stability, impact resistance and response speed, and achieves high functions. Lightweight protective materials improve performance.

CN119192941APending Publication Date: 2024-12-27ZHEJIANG UNIV OF TECH +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411307550.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Domestic shear thickening fluids have shortcomings in the dispersion stability, impact resistance and response speed of nanomaterials. The existing dispersion media have a narrow temperature range and insufficient adhesion, making it difficult to meet the needs of high-strength and lightweight protective materials.

Method used

Using dispersion solvents combined with silicone, hydroxy silicone oil, ethylene glycol, propylene glycol, polyethylene glycol, and other combinations as dispersion medium, the nanoparticles are evenly dispersed to prepare shears with high stability and fast response speed Shear thick fluid, used to prepare materials for high-function bulletproof helmets.

Benefits of technology

It significantly improves the impact resistance and response speed of shear thickened fluids, overcomes the maintenance difficulties and uneven distribution problems of traditional STFs, realizes high-strength and lightweight protective material performance, and improves the intelligence of the overall composite material. and viscosity peak.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192941A_ABST
    Figure CN119192941A_ABST
Patent Text Reader

Abstract

The invention discloses a shear thickening fluid as well as a preparation method and application thereof. The shear thickening fluid comprises nanoparticles and a dispersing solvent, and the dispersing solvent at least comprises an acrylic block low molecular weight copolymer. The nano particles comprise inorganic nano particles and organic nano particles. The shear thickening fluid provided by the invention is higher in response speed and higher in impact resistance; moreover, the novel dispersion medium adopted by the preparation method not only overcomes the problems of difficult maintenance, difficult packaging and non-uniform STF distribution of the traditional STF, but also has the advantages of high impact resistance, high response rate, high intelligent degree and more uniform overall composite material performance, and the liquid-solid response speed and the viscosity peak value are both improved by more than one order of magnitude.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a shear thickening fluid, in particular to a shear thickening fluid and a preparation method and application thereof, belonging to the technical field of protective materials. Background Art

[0002] Shear thickening fluid (STF) is widely considered to have great protective application value due to its unique rheological properties. Compared with conventional metal, inorganic non-metal and other protective equipment, the new flexible protective material based on shear thickening fluid (STF) has the advantages of being light, soft and flexible, and can be covered on the surface of irregular objects, and can effectively resist the impact of high-speed particles.

[0003] In the basic research of STF, the teams of Professor McKinley of MIT and Professor Wagner of the University of Delaware have always been at the forefront of the world. Their research covers the STF stress response mechanism, the relationship between the evolution of nanoparticle structure and performance, the regulation mechanism of STF viscosity curve, the functionalization of nanoparticles, etc., and constantly proposes new design concepts such as lightweight and intelligent STF materials. These works provide solid theoretical and practical support for the development and mass production of protective equipment such as "Liquid Armor" (LiquidArmor) by NASA and the U.S. Army Laboratory (US20060234577, WO2007146703, EP2319880). At present, relevant research and development institutions have innovated the design concept of intelligent nanoparticles, thereby developing high-function, multi-purpose, lightweight STF protective equipment. In China, the China Academy of Engineering Physics, Nanjing University of Science and Technology, Zhejiang University of Technology and other units have also used STF materials based on conventional silica particles and nanoparticles to prepare protective equipment that meets the standards of police bulletproof vests (CN103808210A). Research institutions such as the University of Science and Technology of China and Hebei University of Technology have developed a variety of STFs based on different functional nanoparticles (such as graphene, polyhedral nanoparticles, etc.). The development of lightweight, high-strength STF smart nanocomposites that can withstand ultra-high-speed particle impacts is a cutting-edge direction in the field of protection.

[0004] However, domestic research is still in the tracking state, and there is a huge generation gap between bulletproof products and international technical indicators. Among them, the main problems in the nanomaterial part are: the dispersion stability of nanomaterials needs to be improved; the density, stability, and strength of the instantaneous accumulation agglomeration structure of nanomaterials under the action of local ultra-high stress fields need to be improved; including instantaneous aggregation ability and aggregation structure strength; problems in the dispersion medium part: the existing dispersion medium is mostly a pure organic solvent or a mixture, the applicable temperature range is narrow, and the adhesion with flexible fabrics needs to be improved. Such as: ethylene glycol (EG), propylene glycol (PG), butanediol (BG), the most commonly used is polyethylene glycol (PEG) (single molecular weight or a mixture of different molecular weights), a mixture of poly 3,4-ethylenedioxythiophene and polystyrene sulfonic acid (CN108221382A), etc. At the same time, the shear thickening fluid obtained by the prior art has insufficient response speed, insufficient impact resistance, and migration and leakage problems. Summary of the invention

[0005] The main purpose of the present invention is to provide a shear thickening fluid and a preparation method and application thereof, so as to overcome the deficiencies of the prior art.

[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:

[0007] An embodiment of the present invention provides a shear-thickening fluid, which includes nanoparticles and a dispersion solvent, wherein the dispersion solvent includes at least an acrylic acid block low molecular weight copolymer.

[0008] In some embodiments, the dispersing solvent includes a combination of a first component and a second component, wherein the first component includes any one or a combination of two of silica gel, hydroxy silicone oil, ethylene glycol, propylene glycol, butylene glycol, polyethylene glycol and polypropylene glycol, and the second component includes an acrylic block low molecular weight copolymer.

[0009] In some embodiments, the mass ratio of the first component to the second component is 95:5 to 0:100.

[0010] In some embodiments, the nanoparticles include at least any one of inorganic nanoparticles and organic nanoparticles.

[0011] The embodiment of the present invention further provides a method for preparing the above-mentioned shear thickening fluid, which comprises: uniformly dispersing the nanoparticles in a dispersing solvent to obtain a stably dispersed shear thickening fluid.

[0012] The embodiment of the present invention also provides the use of the aforementioned shear thickening fluid in preparing materials for bulletproof helmets.

[0013] Compared with the prior art, the present invention has at least the following beneficial effects:

[0014] 1) The shear-thickening fluid provided by the present invention has a faster response speed and higher impact resistance;

[0015] 2) The novel dispersion medium used in the preparation method of the shear thickening fluid provided by the present invention not only overcomes the problems of difficult maintenance, difficult packaging, and uneven distribution of STF of traditional STF, but also has the advantages of high impact resistance, fast response rate, high degree of intelligence, and more uniform performance of the overall composite material. The "liquid-solid" response speed and viscosity peak are both improved by more than an order of magnitude. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0017] Figure 1 is the H NMR image characterizing the dispersing solvent component B in Example 1 of the present invention;

[0018] Figure 2 is the H NMR image characterizing the dispersing solvent component B in Example 2 of the present invention;

[0019] Figure 3 is the H NMR image characterizing the dispersing solvent component B in Example 3 of the present invention;

[0020] Figure 4 is the H NMR image characterizing the dispersing solvent component B in Example 4 of the present invention;

[0021] Figure 5 is the H NMR image characterizing the dispersing solvent component B in Example 5 of the present invention;

[0022] Figure 6 is the H NMR image characterizing the dispersing solvent component B in Example 6 of the present invention;

[0023] Figure 7 is the H NMR image characterizing the dispersing solvent component B in Example 7 of the present invention;

[0024] Figure 8 is the H NMR image characterizing the dispersing solvent component B in Example 8 of the present invention;

[0025] Fig. 9 The response speed and viscosity peak curves of the STF samples prepared in Example 1 and Comparative Examples 1-4 of the present invention;

[0026] Fig.10a This is a picture of the impact of tin foil without STF coating;

[0027] Fig.10b This is a diagram showing the impact of the tin foil coated with the traditional STF material in Comparative Example 3;

[0028] Fig.10c This is a diagram showing the state of the tin foil coated with the STF material in Example 1 of the present invention after being impacted. DETAILED DESCRIPTION

[0029] In view of the shortcomings of the prior art, the inventor of this case proposed the technical concept of the present invention after long-term research, which is mainly to provide a shear-thickening fluid with good stability and higher impact strength that can be used in protective materials. The technical solution, its implementation process and principle will be further explained as follows.

[0030] As one aspect of the technical solution of the present invention, a shear thickening fluid is disclosed, including nanoparticles and a dispersion solvent, wherein the dispersion solvent includes a combination of a first component (hereinafter also referred to as "component A") and a second component (hereinafter also referred to as "component B"), the first component includes any one or a combination of two of silica gel, hydroxy silicone oil, ethylene glycol, propylene glycol, butylene glycol, polyethylene glycol and polypropylene glycol, and the second component includes an acrylic block low molecular weight copolymer.

[0031] In some preferred embodiments, the mass ratio of the first component to the second component is 95:5 to 0:100.

[0032] In some preferred embodiments, the weight average molecular weight of the acrylic acid block low molecular weight copolymer is less than 2,000.

[0033] In some preferred embodiments, the mass ratio of the nanoparticles to the dispersion solvent is 10:90 to 90:10.

[0034] In some preferred embodiments, the diameter of the nanoparticles is 10 to 1000 nm.

[0035] In some preferred embodiments, the nanoparticles include at least any one of inorganic nanoparticles and organic nanoparticles.

[0036] As a preferred embodiment of the shear thickening fluid described in the present invention, the inorganic nanoparticles include any one or a combination of two or more of nano-silicon dioxide particles, titanium dioxide particles, calcium carbonate particles, calcium acetate particles, aluminum oxide particles, quartz powder, zinc oxide particles, iron oxide particles, silver particles, ferroferric oxide particles, ZrO2 particles, boric acid, carbon black, graphene, graphene oxide particles, etc., but are not limited to these.

[0037] As a preferred embodiment of the shear thickening fluid of the present invention, the organic nanoparticles include any one or a combination of two or more of polymethyl methacrylate particles, polystyrene particles, polyvinyl chloride particles, starch particles, etc., but are not limited thereto.

[0038] As a preferred embodiment of the shear thickening fluid of the present invention, the nanoparticles are surface functionalized nanoparticles.

[0039] Furthermore, the nanoparticles are partially hollow nanoparticles, and hollowing can achieve lightweight and intelligence.

[0040] Specifically, the aforementioned surface functionalization refers to nanoparticles with special structural functions such as different geometric shapes and hollow structures, which form nanofilling materials with metastable structures of diamond-like crystals. The main feature is that the nanoparticles in the shear-thickening fluid are no longer simply physically stacked under the action of the external field, but through the fluid design and the local high stress brought by the high-speed projectile, the repulsive force is overcome and the potential energy barrier between the particles is broken through, forming a more stable nano-scale to micron-scale solid structure, thereby greatly improving the local impact resistance of the nanomaterial.

[0041] Furthermore, the aforementioned surface functionalization can be functional nanoparticles of different geometric shapes such as rods / needles, sheets, spindles, polyhedrons, etc.

[0042] Furthermore, the agglomerate structure formed by the special structure is similar to the foam-like structural characteristics of a honeycomb, so its theoretical value of specific strength is much higher than that of the conventional spherical nanoparticle stacking structure, achieving the advantage of lightweight while achieving the high functionality of the STF protective material.

[0043] In some more preferred embodiments, the acrylic block low molecular weight copolymer comprises at least a first segment having a controlled molecular weight and position and a second segment having a controlled molecular weight and position; wherein the first segment comprises a segment formed by polymerization of at least any one of the monomers having a structure as shown in formula (I):

[0044]

[0045] Wherein, R includes H or CH3, and X includes a cross-linkable functional group, preferably including any one or a combination of two or more of the cross-linkable silyl, hydroxyl, carboxyl, carbonyl, carbonate, isocyanate, epoxy, vinyl, amino, mercapto, acetoacetyl, alkoxymethylol and cyclic ether groups, but is not limited thereto.

[0046] Furthermore, the second segment includes a segment formed by polymerization of at least any one of the monomers having a structure as shown in formula (II):

[0047]

[0048] Wherein, R1 includes H or CH3, and R2 includes a branched or unbranched saturated alkyl group having 4 to 14 carbon atoms.

[0049] As a preferred embodiment of the shear thickening fluid of the present invention, the second segment of the acrylic block low molecular weight copolymer includes a segment formed by polymerization of any one or a combination of more than two of a plurality of acrylic ester monomers, wherein the acrylic ester monomer includes any one or a mixture of two of acrylic esters and methacrylic esters.

[0050] In some more preferred embodiments, the acrylate includes any one or a combination of two or more of acrylates having a C1-C20 alkyl group, aromatic acrylates, cyclic acrylates, and the like.

[0051] Furthermore, the acrylic acid ester monomer preferably includes any one or a combination of two or more of methyl acrylate, ethyl acrylate, phenyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, n-hexyl acrylate, n-heptyl acrylate, n-octyl acrylate, n-nonyl acrylate, isobornyl acrylate, 2-propylheptyl acrylate, isodecyl acrylate, isostearyl acrylate, etc., but is not limited thereto.

[0052] In some more preferred embodiments, the methacrylate includes any one or a combination of two or more of methacrylate having a C1-C20 alkyl group, aromatic methacrylate, cyclic methacrylate, etc.

[0053] Furthermore, the methacrylate preferably includes any one or a combination of two or more of methyl methacrylate, ethyl methacrylate, butyl methacrylate, 2-ethylhexyl methacrylate, phenyl methacrylate, acetoacetoxyethyl methacrylate, isobornyl methacrylate, isooctyl methacrylate, etc., but is not limited thereto.

[0054] The shear thickening fluid provided by the invention has a faster response speed and higher impact resistance.

[0055] As another aspect of the technical solution of the present invention, it also relates to a method for preparing a shear thickening fluid, which comprises: uniformly dispersing nanoparticles in a dispersing solvent to obtain a stably dispersed shear thickening fluid.

[0056] In some preferred embodiments, the method for preparing the shear thickening fluid specifically comprises the following steps:

[0057] The component B and the component A are fully mixed to obtain a dispersion solvent, and the nanoparticles are then dispersed in the dispersion solvent. The nanoparticles are dispersed evenly to obtain a stably dispersed shear-thickening fluid.

[0058] In summary, through the above technical scheme, the new dispersion medium adopted in the preparation method of the present invention not only overcomes the problems of difficult maintenance, difficult packaging, and uneven distribution of STF in traditional STF, but also has the advantages of high impact resistance, fast response rate, high degree of intelligence, and more uniform performance of the overall composite material. The "liquid-solid" response speed and viscosity peak are both improved by more than an order of magnitude.

[0059] As another aspect of the technical solution of the present invention, it also relates to the use of the aforementioned shear thickening fluid in the preparation of materials for bulletproof helmets.

[0060] Specifically, the application includes: bonding the shear-thickening fluid to a hard material to prepare a material for a bulletproof helmet.

[0061] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification and the drawings.

[0062] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0063] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0064] The inorganic nanoparticles in the present invention include nano silicon dioxide particles, titanium dioxide particles, calcium carbonate particles, calcium acetate particles, aluminum oxide particles, quartz powder, zinc oxide particles, iron oxide particles, silver particles, ferroferric oxide particles, ZrO2 particles, boric acid, carbon black, graphene particles, and graphene oxide particles, all of which are common commercially available products.

[0065] The organic nanoparticles in the present invention include polymethyl methacrylate particles, polystyrene particles, polyvinyl chloride particles, and starch particles, all of which are common commercial products.

[0066] Example 1

[0067] This embodiment provides a method for preparing a shear thickening fluid, the main steps of which are:

[0068] (1) 2 g of polyvinyl pyrrolidone, 0.5 g of azobisisobutylamidine hydrochloride, and 100 ml of distilled water were stirred at room temperature. After the solution was clarified, 11 ml of methyl methacrylate monomer was added and N2 was introduced for 1 h. Then, the mixture was stirred at 65° C. and 200 rpm for 18 h to obtain a polymethyl methacrylate emulsion (PMMA) with an average particle size of about 200 nm.

[0069] 10.0 g of the polymethyl methacrylate emulsion obtained above was taken and dissolved in 80 ml of anhydrous ethanol. After ultrasonic treatment for 1 h, a suspension was obtained after sufficient dissolution. 10 ml of ammonia water was added at 50° C. while stirring. After 10 min, 3 ml of an organic-inorganic silicon source was added. The silicon source was tetraethyl orthosilicate and methyltriethoxysilane in a volume ratio of 1:4. The reaction was carried out for 3 h to obtain silicon dioxide-coated polymethyl methacrylate nanoparticles with an average particle size of 200 nm.

[0070] The silica-coated polymethyl methacrylate nanoparticles obtained above were washed with water and ethanol, centrifuged, dispersed in anhydrous ethanol, poured into a container and spread into a liquid film. After drying, they were soaked in 30 ml of toluene solution for 24 hours, and then the organic solvent was slowly removed. After natural drying, hollow nano-silica was obtained.

[0071] (2) Preparation of dispersion solvent:

[0072] The dispersion solvent consists of two components, A and B, where:

[0073] Component A is propylene glycol, with a mass content of 50wt%;

[0074] Component B is an acrylic acid block low molecular weight copolymer with a weight average molecular weight of less than 2000 and a mass content of 50wt%;

[0075] The preparation method of component B is as follows:

[0076] Methacrylic acid (MAA) (4.3wt%), butyl acrylate (BA) (45.3wt%), ethyl acetate (48.0wt%), dibenzyl trithiocarbonate (DBTTC) (1.5wt%), initiator: 4,4-azobis(4-cyanovaleric acid) (ACPA) (0.9wt%), MAA monomer 20g, and other raw materials are added in proportion. All raw materials are added to a three-necked flask, stirred evenly, and nitrogen is introduced for 30min to deoxygenate. The reaction is carried out at 60°C. After the reaction is completed, the solvent (ethyl acetate) is stripped from the polymer solution at 60°C by rotary evaporation. The weight average molecular weight of the separated polymer is measured to be 1500g / mol. The H nuclear magnetic resonance data of the dispersed solvent component B are: δ0.81-0.95 (16H, 0.88 (dd, J=7.11, 7.11Hz), 0.89 (d, J=6.62Hz)), 1 .29-1.62 (10H, 1.39 (ddq, J=7.11, 7.11, 7.11Hz), 1.39 (ddq, J=7.11, 7.11, 7.11Hz), 1.55 (ddd, J=7.50, 7.40, 7.40Hz), 1.55 (dddd, J=7.50, 7.40, 7.40Hz)), 1.64-1.91 (8H, 1.73 (dddd, J=7.12, 7.12, 7.11, 7.11 Hz), 1.73 (dddd, J=7.12, 7.12, 7.11, 7.11Hz), 1.80 (ddddq, J=7.50, 7.50, 7.40, 7.40, 6.62Hz)), 2.18-2 .32(11H, 2.24(d, J=7.40Hz), 2.24(d, J=7.40Hz), 2.25(dd, J=7.40, 7.40Hz), 2.25(dd, J=7.40, 7.40Hz) ), 4.10-4.23 (5H, 4.17 (dd, J = 7.12, 7.12 Hz), 4.17 (dd, J = 7.12, 7.12 Hz)), 0.89 (16H, m), 1.39 (5H, q, J = 7.10 Hz), 1.55 (5H, q, J = 7.43 Hz), 1.73 (8H, m), 2.24 (11H, m), 4.17 (5H, t, J = 7.11 Hz), the H NMR spectrum showed that the polymer component was successfully prepared, see Figure 1 .

[0077] Component A and component B are mixed and stirred evenly. Component A is 50 g of propylene glycol and component B is 50 g. Stir evenly to obtain a dispersion solvent.

[0078] (3) Preparation of shear-thickening fluid:

[0079] Take 0.5g of hollow nano-silica, add it to 9.5g of the above-mentioned dispersing solvent, and use strong dispersion (stirring speed is 5000r / min, time is 15min) and ultrasonic dispersion (ultrasonic power is 40KHz, time is 20min) to disperse it evenly to obtain a shear thickening fluid.

[0080] Example 2

[0081] This embodiment provides a method for preparing a shear thickening fluid, the main steps of which are:

[0082] (1) Preparation method of rod-shaped nano-silica: 15.00 g of polyvinyl pyrrolidone (number average molecular weight 4000) and 150 ml of n-pentanol were ultrasonically dissolved and mixed well. 15 ml of ethanol, 4.2 ml of water, and 1.5 ml of 0.18 mol / L sodium citrate solution were added and manually shaken. 3 ml of ammonia water (mass percentage concentration of 26%) was added and manually shaken. Then 1.5 ml of tetraethyl orthosilicate (TEOS) was added and manually shaken. After being manually shaken, the mixture was placed in a water bath at 40° C. and allowed to stand for 30 min. The mixture was taken out and centrifuged and washed to obtain rod-shaped nano-silica;

[0083] (2) Preparation of dispersion solvent:

[0084] The dispersion solvent consists of two components, A and B, where:

[0085] Component A is silica gel, with a mass content of 95wt%;

[0086] Component B is an acrylic acid block low molecular weight copolymer with a weight average molecular weight of less than 2000 and a mass content of 5wt%;

[0087] The preparation method of component B is as follows:

[0088] Allyl isocyanate (20.0wt%), phenyl acrylate (29.6wt%), ethyl acetate (48.0wt%), dibenzyl trithiocarbonate (1.5wt%), initiator: azobisisobutyronitrile (AIBN) (0.9wt%), phenyl acrylate monomer 20g, and other raw materials are added in proportion. All raw materials are added to a three-necked flask, stirred evenly, and nitrogen is introduced for 30 minutes to deoxygenate. The reaction is carried out at 60°C. After the reaction is completed, the solvent (ethyl acetate) is stripped from the polymer solution at 60°C by rotary evaporation. The weight average molecular weight of the separated polymer is measured to be 1600g / mol. The H NMR spectrum shows that the polymer component is successfully prepared. Figure 2 .

[0089] Component A and component B are mixed and stirred evenly, component A is 95g, component B is 5g, and stirred evenly to obtain a dispersion solvent.

[0090] (3) Preparation of shear-thickening fluid:

[0091] Take 1.0g of rod-shaped nano-silica, add it to 9.0g of the above-mentioned dispersing solvent, and use strong dispersion (stirring speed is 5000r / min, time is 15min) and ultrasonic dispersion (ultrasonic power is 40KHz, time is 20min) to disperse it evenly to obtain a shear thickening fluid.

[0092] Example 3

[0093] This embodiment provides a method for preparing a shear thickening fluid, the main steps of which are:

[0094] (1) Preparation method of hollow rod-shaped ferrosoferric oxide: 15.00 g of polyvinyl pyrrolidone (number average molecular weight 4000) and 150 ml of n-pentanol were dissolved by ultrasonication. After mixing evenly, 15 ml of ethanol, 4.2 ml of water, and 1.5 ml of 0.18 mol / L sodium citrate solution were added and manually shaken. Then, 3 ml of ammonia water (mass percent concentration of 26%) was added and manually shaken. Then, 1.5 ml of tetraethyl orthosilicate (TEOS) was added and manually shaken. After being manually shaken, the mixture was placed in a water bath at 40° C. and allowed to stand for 30 min. The mixture was taken out and centrifuged and washed to obtain rod-shaped silica.

[0095] Dissolve 0.318g of trisodium citrate dihydrate in 20ml of ethylene glycol, then add 1.5g of anhydrous sodium acetate and 0.75g of deionized water, which is referred to as solution A; dissolve 0.819g of ferric chloride in 10ml of ethylene glycol, and continue to add 0.5ml of 5wt% rod-shaped silica aqueous solution, which is referred to as solution B; mix solution A and solution B, stir to fully mix to obtain a brown-black clear solution and place it in a high-temperature and high-pressure reactor with a volume of 50ml, set the temperature to 200℃, and react at this temperature for 10h. After the reaction is completed, separate and wash the obtained mixed solution to obtain rod-shaped silica coated with ferrosoferric oxide;

[0096] The rod-shaped silicon dioxide coated with ferroferric oxide was dissolved in a 5 mol / L sodium hydroxide aqueous solution and reacted with magnetic stirring for 10 h in a 55°C water bath. After the reaction was completed, the product was centrifuged and washed several times with deionized water and anhydrous ethanol to obtain the final product.

[0097] (2) Preparation of dispersion solvent:

[0098] The dispersion solvent consists of two components, A and B, where:

[0099] Component A is hydroxy silicone oil, with a mass content of 70wt%;

[0100] Component B is an acrylic acid block low molecular weight copolymer with a weight average molecular weight of less than 2000 and a mass content of 30wt%;

[0101] The preparation method of component B is as follows:

[0102] Ethoxycarbonyl propylene (10.2wt%), 2-ethylhexyl acrylate (39.4wt%), ethyl acetate (48wt%), dibenzyl trithiocarbonate (1.5wt%), initiator: azobisisobutyronitrile (0.9wt%), ethoxycarbonyl propylene monomer 20g, and other raw materials are added in proportion. All raw materials are added to a three-necked flask, stirred evenly, and nitrogen is introduced for 30 minutes to deoxygenate. The reaction is carried out at 60°C. After the reaction is completed, the solvent (ethyl acetate) is stripped from the polymer solution by rotary evaporation at 60°C. The weight average molecular weight of the separated polymer is measured to be 1800g / mol. The H NMR spectrum shows that the polymer component is successfully prepared. Figure 3 .

[0103] Component A and component B are mixed and stirred evenly, component A is 70g, component B is 30g, and stirred evenly to obtain a dispersion solvent.

[0104] (3) Preparation of shear-thickening fluid:

[0105] Take 2.0g of rod-shaped silicon dioxide coated with ferrosoferric oxide, add it to 8.0g of the above-mentioned dispersing solvent, and use strong dispersion (stirring speed is 5000r / min, time is 15min) and ultrasonic dispersion (ultrasonic power is 40KHz, time is 20min) to disperse it evenly to obtain a shear thickening fluid.

[0106] Example 4

[0107] This embodiment provides a method for preparing a shear thickening fluid, the main steps of which are:

[0108] (1) Preparation of graphene oxide: 30 mg of graphene oxide was weighed and dispersed in 300 ml of an alcohol solution of 1% by volume of 3-mercaptopropylethoxysilane, and stirred continuously at room temperature for 24 h. Then, the thiol-modified graphene oxide material was washed and separated.

[0109] (2) Preparation of dispersion solvent:

[0110] The dispersion solvent consists of two components, A and B, where:

[0111] Component A is ethylene glycol, with a mass content of 20wt%;

[0112] Component B is an acrylic acid block low molecular weight copolymer with a weight average molecular weight of less than 2000 and a mass content of 80wt%;

[0113] The preparation method of component B is as follows:

[0114] Propylene oxide (15.8 wt%), n-hexyl acrylate (33.7 wt%), ethyl acetate (48 wt%), dibenzyl trithiocarbonate (1.5 wt%), initiator: benzoyl peroxide (BPO) (1.0 wt%), 20 g of propylene oxide monomer, and other raw materials added in proportion. All raw materials were added to a three-necked flask, stirred evenly, and nitrogen was introduced for 30 minutes to deoxygenate. The reaction was carried out at 70°C. After the reaction was completed, the solvent (ethyl acetate) was stripped from the polymer solution by rotary evaporation at 70°C. The weight average molecular weight of the separated polymer was measured to be 1600 g / mol. The H NMR spectrum showed that the polymer component was successfully prepared. Figure 4 .

[0115] Component A and component B are mixed and stirred evenly. Component A is 20 g and component B is 80 g. Stir evenly to obtain a dispersion solvent.

[0116] (3) Preparation of shear-thickening fluid:

[0117] Take 5.0 g of thiol-modified graphene oxide material, add it to 5.0 g of the above-mentioned dispersing solvent, and use strong dispersion (stirring speed is 5000 r / min, time is 15 min) and ultrasonic dispersion (ultrasonic power is 40 KHz, time is 20 min) to disperse it evenly to obtain a shear thickening fluid.

[0118] Example 5

[0119] This embodiment provides a method for preparing a shear thickening fluid, the main steps of which are:

[0120] (1) Preparation of polymethyl methacrylate particles:

[0121] Weigh 200g of methyl methacrylate monomer, add 500ml of deionized water, pour into a 2L four-necked flask, stir evenly at 800r / min on an electric stirrer, and slowly add 5g of azobisisobutyronitrile initiator into the four-necked flask. Place the four-necked flask in an oil bath set at 80°C, and continue stirring to react for 3h. Pour the reaction product into a large amount of ethanol (about 500ml) for precipitation, then use a vacuum filtration device to filter and collect the precipitate. Wash the precipitate several times with ethanol to remove unreacted monomers and impurities, and dry the washed product in a vacuum drying oven at 60°C for 8h to obtain polymethyl methacrylate particles.

[0122] (2) Preparation of dispersion solvent:

[0123] The dispersing solvent is composed of component B, which is an acrylic acid block low molecular weight copolymer with a weight average molecular weight lower than 2000;

[0124] The preparation method of component B is as follows:

[0125] Allylamine (30.2wt%), isooctyl methacrylate (19.1wt%), ethyl acetate (48wt%), dibenzyl trithiocarbonate (1.5wt%), initiator: benzoyl peroxide (1.2wt%), 20g of allylamine monomer, and other raw materials added in proportion. All raw materials were added to a three-necked flask, stirred evenly, and nitrogen was introduced for 30 minutes to deoxygenate. The reaction was carried out at 70°C. After the reaction was completed, the solvent (ethyl acetate) was stripped from the polymer solution by rotary evaporation at 70°C. The weight average molecular weight of the separated polymer was measured to be 1500g / mol. The nuclear magnetic resonance spectrum showed that the polymer component was successfully prepared. Figure 5 .

[0126] (3) Preparation of shear-thickening fluid:

[0127] Take 8.0g of polymethyl methacrylate particles, add them into 2.0g of the above-mentioned dispersing solvent, and disperse them evenly by strong dispersion (stirring speed is 5000r / min, time is 15min) and ultrasonic dispersion (ultrasonic power is 40KHz, time is 20min) to obtain a shear thickening fluid.

[0128] Example 6

[0129] This embodiment provides a method for preparing a shear thickening fluid, the main steps of which are:

[0130] (1) Preparation of polystyrene particles:

[0131] Add 500ml of deionized water to a four-necked flask, then add 10g of sodium dodecyl sulfate, stir it with an electric stirrer at a speed of 800r / min to fully dissolve it, then weigh 200g of styrene monomer, slowly add it dropwise to the above solution, and continue stirring for 30min to mix the system evenly. Place the four-necked flask in a constant temperature water bath, heat it to 70°C, and after the temperature stabilizes, add 5g of potassium persulfate initiator to the flask to start the polymerization reaction, and the reaction time is 4h. After the reaction is completed, the product is cooled to room temperature, and the product is filtered using a Buchner funnel and a suction flask to collect the solid product. Wash the collected product with a large amount of deionized water to remove unreacted monomers and impurities. Put the washed product into a drying oven and dry it at 60°C for 8h to obtain polystyrene particles.

[0132] (2) Preparation of dispersion solvent:

[0133] The dispersing solvent is composed of component B, which is an acrylic acid block low molecular weight copolymer with a weight average molecular weight lower than 2000;

[0134] The preparation method of component B is as follows:

[0135] Allyl mercaptan (13.6wt%), 2-propylheptyl acrylate (36wt%), toluene (48wt%), dibenzyl trithiocarbonate (1.5wt%), initiator: benzoyl peroxide (0.9wt%), propylene mercaptan monomer 20g, and other raw materials added in proportion; all raw materials are added into a three-necked flask, stirred continuously and evenly, nitrogen is introduced for 30min to deoxygenate, and the reaction is carried out at 60°C. After the reaction is completed, the solvent (toluene) is stripped from the polymer solution by rotary evaporation at 60°C, and the weight average molecular weight of the separated polymer is measured to be 1800g / mol. The H NMR spectrum shows that the polymer component is successfully prepared. Figure 6 .

[0136] (3) Preparation of shear-thickening fluid:

[0137] Take 9.0g of polystyrene particles, add them into 1.0g of the above-mentioned dispersing solvent, and disperse them evenly by strong dispersion (stirring speed is 5000r / min, time is 15min) and ultrasonic dispersion (ultrasonic power is 40KHz, time is 20min) to obtain a shear thickening fluid.

[0138] Example 7

[0139] This embodiment provides a method for preparing a shear thickening fluid, the main steps of which are:

[0140] (1) Preparation of polyvinyl chloride particles:

[0141] Add 500ml of deionized water to a four-necked flask, then add 10g of polyvinyl alcohol, stir it with an electric stirrer at a speed of 800r / min to fully dissolve it, then weigh 200g of vinyl chloride monomer, slowly add it dropwise to the above solution, and continue stirring for 30min to mix the system evenly. Place the four-necked flask in a constant temperature water bath and heat it to 50°C. After the temperature stabilizes, add 5g of diisopropyl peroxydicarbonate initiator to the flask to start the polymerization reaction, and the reaction time is 5h. After the reaction is completed, use a Buchner funnel and a suction flask to filter the product, collect the solid product, and wash the collected product with a large amount of deionized water to remove unreacted monomers and impurities. Put the washed product into a drying oven and dry it at 50°C for 10h to obtain polyvinyl chloride particles.

[0142] (2) Preparation of dispersion solvent:

[0143] The dispersion solvent consists of two components, A and B, where:

[0144] Component A is polyethylene glycol, with a mass content of 10wt%;

[0145] Component B is an acrylic acid block low molecular weight copolymer with a weight average molecular weight of less than 2000 and a mass content of 90wt%;

[0146] The preparation method of component B is as follows:

[0147] N-vinyl acetyl (12.5wt%), acetoacetoxyethyl methacrylate (37.3wt%), toluene (48wt%), dibenzyl trithiocarbonate (DBTTC) (1.2wt%), initiator: benzoyl peroxide (BPO) (1.0wt%), N-vinyl acetyl monomer 20g, and other raw materials are added in proportion. All raw materials are added to a three-necked flask, stirred evenly, and nitrogen is introduced for 30 minutes to deoxygenate. The reaction is carried out at 80°C. After the reaction is completed, the solvent (toluene) is stripped from the polymer solution by rotary evaporation at 80°C. The weight average molecular weight of the separated polymer is measured to be 1700g / mol. The H NMR spectrum shows that the polymer component is successfully prepared. Figure 7 .

[0148] Component A and component B are mixed and stirred evenly, component A is 10g, component B is 90g, and stirred evenly to obtain a dispersion solvent.

[0149] (3) Preparation of shear-thickening fluid:

[0150] Take 9.0g of polyvinyl chloride particles, add them into 1.0g of the above-mentioned dispersing solvent, and disperse them evenly by strong dispersion (stirring speed is 5000r / min, time is 15min) and ultrasonic dispersion (ultrasonic power is 40KHz, time is 20min) to obtain a shear thickening fluid.

[0151] Example 8

[0152] This embodiment provides a method for preparing a shear thickening fluid, the main steps of which are:

[0153] (1) Starch granule preparation:

[0154] Weigh 20g starch, add 300ml deionized water, stir evenly at 500r / min on a magnetic stirrer to prepare a starch solution with a concentration of about 6.7%. Slowly add 5g sodium hydroxide solution dropwise to the above starch solution, and use a pH meter to monitor the pH value of the solution and adjust it to between 9-10. Transfer the solution with adjusted pH value to a 1L autoclave and seal it, set the temperature to 150°C, the pressure to 2MPa, and react for 2h. After the reaction is completed, let the reactor cool naturally to room temperature, open the lid of the reactor and take out the reaction product. Pour the product into about 300ml ethanol and wash it several times until the washing liquid is colorless to remove unreacted substances and impurities. Then put the washed product into a centrifuge, centrifuge it at 8000rpm for 15min, and collect the precipitate. Finally, put the precipitate into a dialysis bag, dialyze it in 1000ml deionized water for 12h, and replace the deionized water every 4h to remove residual small molecules to obtain pure nano starch particles.

[0155] (2) Preparation of dispersion solvent:

[0156] The dispersion solvent consists of two components, A and B, where:

[0157] Component A is polypropylene glycol, with a mass content of 40wt%;

[0158] Component B is an acrylic acid block low molecular weight copolymer with a weight average molecular weight of less than 2000 and a mass content of 60wt%;

[0159] The preparation method of component B is as follows:

[0160] 2-methoxypropylene (22.6wt%), isobornyl methacrylate (27.2wt%), toluene (48wt%), dibenzyl trithiocarbonate (DBTTC) (1.2wt%), initiator: benzoyl peroxide (BPO) (1.0wt%), 2-methoxypropylene monomer 20g, and other raw materials are added in proportion. All raw materials are added to a three-necked flask, stirred evenly, and nitrogen is introduced for 30 minutes to deoxygenate. The reaction is carried out at 80°C. After the reaction is completed, the solvent (toluene) is stripped from the polymer solution by rotary evaporation at 80°C. The weight average molecular weight of the separated polymer is measured to be 1800g / mol. The H NMR spectrum shows that the polymer component is successfully prepared. Figure 8 .

[0161] Component A and component B are mixed and stirred evenly. Component A is 40 g and component B is 60 g. Stir evenly to obtain a dispersion solvent.

[0162] (3) Preparation of shear-thickening fluid:

[0163] Take 6.0g of starch granules, add them into 4.0g of the above-mentioned dispersing solvent, and disperse them evenly by strong dispersion (stirring speed is 5000r / min, time is 15min) and ultrasonic dispersion (ultrasonic power is 40KHz, time is 20min) to obtain a shear thickening fluid.

[0164] Comparative Example 1

[0165] The only difference between this comparative example and Example 1 is that the dispersing solvent in step (2) is completely replaced by polyethylene glycol (weight average molecular weight is 2000), and the other conditions are the same as Example 1 to obtain a shear thickening fluid.

[0166] Comparative Example 2

[0167] The only difference between this comparative example and Example 1 is that the dispersing solvent in step (2) is completely replaced by ethylene glycol. The other conditions are the same as those in Example 1, and a shear thickening fluid is obtained.

[0168] The inventors of this case have studied the response speed and peak viscosity of the shear thickening fluid sample prepared in Example 1 (using TA's ARES rheometer, tested at room temperature 25°C, using the steady-state shear mode, and the shear rate set to 10 -1 ~10 3 1 / s, all data detection conditions are the same) for testing, please refer to the test results Fig. 9 Curve 1 in .

[0169] For the test results of the response speed and viscosity peak of the sample prepared in Example 1, please refer to Fig. 9 Curve 3 in .

[0170] For the test results of the response speed and viscosity peak of the sample prepared in Example 2, please refer to Fig. 9 From curve 5 in the figure, we can see that the viscosity and response speed of the sample are lower, and there is no response at high shear speed.

[0171] Comparative Example 3

[0172] Traditional STF materials:

[0173] The solvent is polyethylene glycol (weight average molecular weight 2000), the nano material is nano silicon dioxide particles (particle size 100 nm), the addition amount is 5wt%, and the mixture is evenly mixed to obtain a traditional STF material (the specific preparation process is the same as that in Example 1).

[0174] For the test results of the response speed and viscosity peak of the samples prepared in this comparative example, please refer to Fig. 9 Curve 4 in .

[0175] When STF material is coated on the surface of tin foil (coating thickness 50 microns), the tin foil is subjected to an impact test (500g load, 10 joules kinetic energy impact, material appearance). For a comparison of the impact effects on tin foil, please refer to Figure 10a-Figure 10c .in, Fig.10a This is a picture of the impact of tin foil without STF material coating. Fig.10b This is a picture of the impact of tin foil coated with traditional STF material. Fig.10c This is a picture of the tin foil coated with the STF material in Example 1 after being impacted; it can be seen that the traditional STF material will still break after being impacted, while the STF material in the present invention can prevent the tin foil from being penetrated by the impacting object and maintain its morphology.

[0176] Comparative Example 4

[0177] The difference between this comparative example and Example 1 is that the hollow nano-silicon dioxide is replaced by ordinary nano-silicon dioxide (particle size is 100 nm), and the other conditions are the same as Example 1 to obtain a shear thickening fluid. The test results of the response speed and viscosity peak of the samples obtained in this comparative example can be found in Fig. 9 From curve 2 in the figure, we can see that the viscosity and response speed of the sample are relatively low.

[0178] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification. For example, in addition to the nanoparticles listed in Examples 1-8, they were replaced with titanium dioxide particles, calcium carbonate particles, calcium acetate particles, aluminum oxide particles, quartz powder, zinc oxide particles, iron oxide particles, silver particles, ZrO2 particles, boric acid, carbon black, etc., and experiments were also conducted, and relatively ideal results were obtained.

[0179] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.

Claims

1. A shear-thickening fluid, characterized in that: include: Nanoparticles and a dispersing solvent, wherein the dispersing solvent at least comprises an acrylic acid block low molecular weight copolymer.

2. The shear thickening fluid according to claim 1, characterized in that: The dispersing solvent comprises a combination of a first component and a second component, wherein the first component comprises any one or a combination of two of silica gel, hydroxy silicone oil, ethylene glycol, propylene glycol, butylene glycol, polyethylene glycol and polypropylene glycol, and the second component comprises an acrylic acid block low molecular weight copolymer; And / or, the weight average molecular weight of the acrylic acid block low molecular weight copolymer is lower than 2,000.

3. The shear thickening fluid according to claim 2, characterized in that: The mass ratio of the first component to the second component is 95:5 to 0:100; And / or, the mass ratio of the nanoparticles to the dispersion solvent is 10:90 to 90:10; and / or, the diameter of the nanoparticles is 10 to 1000 nm.

4. The shear thickening fluid according to claim 1, characterized in that: The nanoparticles include at least any one of inorganic nanoparticles and organic nanoparticles. The inorganic nanoparticles include any one of nano silicon dioxide particles, titanium dioxide particles, calcium carbonate particles, calcium acetate particles, aluminum oxide particles, quartz powder, zinc oxide particles, iron oxide particles, silver particles, ferroferric oxide particles, ZrO2 particles, boric acid, carbon black, graphene, and graphene oxide particles, or a combination of two or more thereof. The organic nanoparticles include any one of polymethyl methacrylate particles, polystyrene particles, polyvinyl chloride particles, and starch particles, or a combination of two or more thereof. And / or, the nanoparticles are surface functionalized nanoparticles; And / or, the nanoparticles are hollow nanoparticles.

5. The shear thickening fluid according to claim 1, characterized in that The acrylic block low molecular weight copolymer comprises at least a first segment having a controlled molecular weight and position and a second segment having a controlled molecular weight and position; wherein the first segment comprises a segment formed by polymerization of at least any one of the monomers having a structure as shown in formula (I): Wherein, R includes H or CH3, and X includes any one or a combination of two or more of a cross-linkable silyl group, a hydroxyl group, a carboxyl group, a carbonyl group, a carbonate group, an isocyanate group, an epoxy group, a vinyl group, an amino group, a mercapto group, an acetoacetyl group, an alkoxymethylol group, and a cyclic ether group; The second segment includes a segment formed by polymerization of at least one of the monomers having a structure as shown in formula (II): Wherein, R1 includes H or CH3, and R2 includes a branched or unbranched saturated alkyl group having 4 to 14 carbon atoms.

6. The shear thickening fluid according to claim 5, characterized in that: The second segment of the acrylic acid block low molecular weight copolymer includes a segment formed by polymerization of any one or a combination of two or more of a plurality of acrylic acid ester monomers, wherein the acrylic acid ester monomer includes any one or a combination of two of acrylic acid ester and methacrylic acid ester; The acrylate includes any one or a combination of two or more of acrylates having a C1-C20 alkyl group, aryl acrylates, and cyclic acrylates; the methacrylate includes any one or a combination of two or more of methacrylates having a C1-C20 alkyl group, aryl methacrylates, and cyclic methacrylates.

7. The shear thickening fluid according to claim 6, characterized in that: The acrylic acid ester includes any one or a combination of two or more of methyl acrylate, ethyl acrylate, phenyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, n-hexyl acrylate, n-heptyl acrylate, n-octyl acrylate, n-nonyl acrylate, isobornyl acrylate, 2-propylheptyl acrylate, isodecyl acrylate, and isostearyl acrylate; And / or, the methacrylate includes any one or a combination of two or more of methyl methacrylate, ethyl methacrylate, butyl methacrylate, 2-ethylhexyl methacrylate, phenyl methacrylate, acetoacetoxyethyl methacrylate, isobornyl methacrylate, and isooctyl methacrylate.

8. The method for preparing a shear thickening fluid according to any one of claims 1 to 7, characterized in that: include: The nanoparticles are uniformly dispersed in a dispersing solvent to obtain a stably dispersed shear-thickening fluid.

9. Use of the shear thickening fluid according to any one of claims 1 to 7 in preparing materials for bulletproof helmets.

10. A material for a bulletproof helmet, characterized in that: It is made by laminating a hard material with the shear thickening fluid described in any one of claims 1-7.

Citation Information

Patent Citations

  • Preparation method of shock-resistant STF (shear thickening fluid) gel

    CN106674421A

  • Optically clear shear thickening fluids and optical display device comprising same

    CN113372783A

  • Stab-resistant bulletproof fabric based on shear thickening fluid and preparation method of stab-resistant bulletproof fabric

    CN114507986A

  • Anti-settling shear thickening electrolyte and preparation method thereof

    CN117913364A

  • Optically clear shear thickening fluids and optical display device comprising same

    US20210277219A1